(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
As the importance of marine energy development increases, deep-sea aquaculture net cages, critical for improving energy efficiency and modernizing fisheries, face challenges such as high power supply costs, maintenance difficulties, and environmental impact. This paper proposes a Two-wing Pendulum Wave Energy Converter (TPWEC) suitable for offshore deep-sea regions. The device captures wave energy through a pendulum wing system, converting it into electricity to support deep-sea aquaculture, while efficiently utilizing marine resources. A three-dimensional numerical wave tank is developed based on viscous flow theory, and convergence analysis is performed using the k-ε turbulence model. The hydrodynamic and energy conversion characteristics of the TPWEC under various sea conditions are analyzed. The results show that the shape of the pendulum wings significantly impacts energy capture. Within a reasonable range, increasing the wing width enhances the wave moment and captured energy, but the rate of increase becomes slower as the width grows. Regarding the PTO damping constant, the system’s average power output increases with linear damping up to an optimal point, then decreases. The optimal damping constants vary between 2.5 and 7.5 N·m·s/rad depending on the wave period. Additionally, the spacing between the TPWEC and the aquaculture float structure significantly affects its hydrodynamic response. The motion response is largest when the spacing ratio (D/a) is 1.5. The energy capture efficiency is also influenced by the number and relative positioning of the devices. Maximum energy capture is achieved when six devices are placed symmetrically on both sides of the net cage. Simulation results from Comsol software further confirm the energy output characteristics of the TPWEC. This study concludes that the TPWEC offers high energy efficiency and environmental adaptability, providing a viable solution for integrating renewable energy generation with deep-sea aquaculture systems.